Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am having a problem with the following exercise. I have to determine the function f such that:

$$f'(x^2)=\frac{1}{x} \text{ for } x>0, \quad f(1)=1$$

Thank you in advance

share|improve this question
    
Please, try to make the title of your question more informative. E.g., Why does $a<b$ imply $a+c<b+c$? is much more useful for other users than A question about inequality. From How can I ask a good question?: Make your title as descriptive as possible. In many cases one can actually phrase the title as the question, at least in such a way so as to be comprehensible to an expert reader. –  Julian Kuelshammer Nov 7 '12 at 20:19

3 Answers 3

up vote 0 down vote accepted

$$\dfrac{df(x^2)}{dx} = \dfrac{df(x^2)}{d(x^2)} \dfrac{d(x^2)}{dx} = 2x \dfrac{df(y)}{dy}$$ where $y=x^2$. Hence, we get that $$\dfrac1{\sqrt{y}} = \dfrac1{x} = \dfrac{df(x^2)}{dx} = 2\sqrt{y} \dfrac{df(y)}{dy}$$ Hence, we have $$\dfrac{df(y)}{dy} = \dfrac1{2y}$$ This gives us that $f(y) = \dfrac{\log(y)}2 + C$. Since $f(1) = 1$, we get that $C=1$. Hence, we have $$f(y) = \dfrac{\log(y)}2 +1$$

share|improve this answer
    
How did you get what $\frac{1}{x}$ is ? –  Belgi Nov 7 '12 at 20:34
    
I read $f'(x^2)$ as the derivative of $f$ evaluated at $x^2$. That is, $f'(x)=\frac1{\sqrt{x}}$. –  robjohn Nov 7 '12 at 20:41
    
Marvis, note the OP wrote $f'(x^2)$ and not $f(x^2)'=f'(x^2)2x$ You're interpreting this as the latter, but I think it is not the case. –  Pedro Tamaroff Nov 7 '12 at 20:51

$f '(x^2)=1/x \Rightarrow$ if you only plug in $x$ to the function $f '$ this yields the mentioned $f '(x)=x^{-1/2}$.

integrating this gives you $f(x)=2x^{1/2}+C$.

now adjust the const so that $f(x)=1$ where $x=1$. (you might find something like -1...)

Cheers Fab

share|improve this answer

We have $xf'(x^2)=1$. Let $g(x)=f(x^2)$. Then $g'(x)=2xf'(x^2)$. So the original condition reads $$ g'(x)=2. $$ This tells us that $g(x)=2x+c$ for some constant $c$. But then, as we consider positive $x$, $$ f(x)=f((\sqrt x)^2)=g(\sqrt x)=2{\sqrt x}+c. $$ As $f(1)=1$, we have $1=2+c$, so $c=-1$. Then $$ f(x)=2\sqrt x - 1 $$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.